PENGARUH HARGA PRODUK TERHADAP KEPUASAN KONSUMEN WARDAH PADA MAHASISWI PENDIDIKAN EKONOMI FKIP UNIVERSITAS RIAU - Dewi Ayuni; Sakdanur Nas; Hendripides Hendripides (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
bstract: This research aims to find out the effect of product prices on consumer satisfaction wardah on students of Economic Education FKIP University riau. The population in this study was a student of Economic Education FKIP University of Riau who used wardah products as many as 162 female students. The study sample numbered 62 female students who used proportional random sampling techniques. To determine the size of the number of samples using the formula slovin. The method of data collection in this study is to use a questionnaire. This questionnaire is used to obtain research data on product prices and consumer satisfaction. The questionnaire is distributed through google form media and the collected data is then tabulated and analyzed using simple linear regression with the help of SPSS version 22. The results showed that the price variables of the product had a positive and significant effect on consumer satisfaction in FKIP Economics Education students of Riau University. Based on the results of the R2 test, information was obtained that the value of R2 amounted to 0.533 or 53.3%. This means that the percentage of influence exerted by independent variables (product prices) on dependent variables (consumer satisfaction) is 53.3%. The remaining 46.7% were affected by other variables, namely product quality, brand image, quality of service and emotions that were not studied in the study. The study is still not perfect so it is hoped that further researchers can conduct more thorough research on other factors that affect consumer satisfaction and can increase or expand the population and sample of the study.Key Words: Product Price, Consumer Satisfaction